Distribution of Cardiovascular Disease and Associated Risk Factors by County Type and Health Insurance Status: Results from the 2008 Ohio Family Health Survey. (January 2015) - Kariisa, Mbabazi; Seiber, Eric
Objectives: Epidemiologic studies have documented a disproportionate burden of chronic diseases in Appalachia, showing the area to be underserved by the health-care system. Nothing is known about how the health status of the Appalachian population compares with other rural or non-rural populations in the same state. We examined the associations among county type, health insurance category, and health outcomes in poorer adult Ohioans. Methods: We obtained data from the 2008 Ohio Family Health Survey, a complex landline- and cell phone-based survey of 50, 944 noninstitutionalized households. We constructed bivariate analyses examining health status measures across various insurance categories and metropolitan, suburban, rural, and Appalachian counties in Ohio. Results: Medicaid enrollees living in Appalachian and rural counties tended to be in poorer health and have a greater prevalence of smoking than non-Medicaid enrollees. Within rural and Appalachian regions, Medicaid enrollees were more likely than non-Medicaid enrollees to have lower self-rated health (54.8%, 95% confidence interval [CI] 44.1, 65.5 in rural regions and 52.1%, 95% CI 44.7, 59.5 in Appalachian regions). Appalachian and rural Medicaid enrollees were at an increased likelihood of having several chronic diseases compared with non-Medicaid enrollees. Conclusion: Our findings suggest that rural and Ohio Appalachian Medicaid enrollees were more likely to have hypertension, cardiovascular disease, and overall poorer health than non-Medicaid enrollees. These findings have important policy implications for health-care reform, highlighting regional disparities in provider coverage. These underserved regions would need an increase in the provider base to positively impact proposed Medicaid expansion programs.